(untitled) (Third Sector Social Economic Review, 2022)
Social media tools have turned into an entrepreneurship platform for women because of their advantages. In this study, we aim to determine the socio-demographic characteristics and entrepreneurial typologies of women entrepreneurs engaging in entrepreneurial activities on Instagram. To this end, we examine interviews (N = 144) published on a website. We determine the typology of women social media entrepreneurship by classifying the interviews in terms of the narratives of decision of becoming an entrepreneur. Also, we compile the demographic characteristics of the entrepreneurs from the interviews. The findings show that women social media entrepreneurs are generally between the ages of 31-40, have a bachelor’s degree or higher, and are married. In terms of entrepreneurial decision-making stories, we cluster these entrepreneurs under six categories as “encouraged by others”, “discovering their own potential”, “not happy in their previous job”, “following their dreams”, “entrepreneurs by chance” and “entrepreneurs after having children”. The findings differ from previous studies in terms of highlighting the role of social media in entrepreneurial decisions whereas are similar to previous studies in terms of the effect of such factors as the need for autonomy, motherhood roles, and commitment to entrepreneurial ideals on entrepreneurial decisions.